Body temperature and dehydration rate in adolescents undergoing the Cooper’s 12-minute run test - Lima, William Alves; Bezerra, Yara; Soares, Viviane; Silva, Iransé Oliveira; Tolentino, Grassyara Pinho; Júnior, Jairo Teixeira; Faria, Margareth; Venâncio, Patrícia Espíndola Mota (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: During the practice of any physical exercises is produced heat. About 30% of this heat is transformed into work and the other 70%, distributed to the body, thus increasing the body temperature of the individual. Objective: to identify changes in body temperature and hydration of adolescents classified as physically actives or inactives. Methods: This is a cross-sectional, quantitative, descriptive study with 40 students (13-17 years old) from a private school in Anápolis-GO. The tympanic and forehead body temperature and body mass were measured. The urine produced was then collected and the hydration state was estimated before and after the 12-minute run test, which was used to calculate the VO2max. After checking the normality of the data, the paired “t” test was performed to compare the pre and post-run data and a “t” test for independent samples to compare the groups denominated: active and inactive. Results: there was no significant difference in relation to the temperature pre-and post-test of the Cooper protocol in active and inactive individuals, but the active group had a higher central temperature. The active group presented a greater reduction of body mass and a worse state of dehydration, evaluated by the urine color, and also by the calculation of the rate of sweating. Finally, although both groups received the classification of “weak” regarding aerobic capacity, the active group was significantly superior to the inactive group. Conclusion: the group of actives adolescents presented higher central body temperature, with a higher rate of sweating, due to their greater physical effort (better test performance) and their better training, which can lead to a better body cooling system.